Simultaneous Determination of Nine Components in Ligustri Lucidi Fructus from Different Habitats by UPLC-ECD - Zeli CHUN; Ya ZHU; Rongxiang CHEN (Shipin gongye ke-ji, 2022)
A method was devoloped for the determination of hydroxytyrosol, protocatechuic acid, tyrosol, salidroside, verbascoside, specnuezhenide, luteolin, oleuropein and rutin in Ligustri Lucidi Fructus from different habitats by ultra-high performance liquid chromatography-electrochemical detection (UPLC-ECD). Ligustri Lucidi Fructus powder (0.25 g) was extracted ultrasonically for 20 min with 10 mL of 80% methanol. The extract was filtered through microporous membrane of 0.22 μm and then separeted by a Waters ACQUITY UPLC BEH shield RP 18 (2.1 mm×100 mm, 1.7 μm) chromatographic column. Methanol−50 mmol·L−1 potassium citrate solution with gradient elution was employed as the mobile phase. The flow rate was 0.4 mL·min−1, the column temperature was maintained at 45 ℃ and the injection volume was 1 μL. The potential of electrochemical detector was set at 450 mV in the first channel and 700 mV in the second channel. The results showed that the linearity of nine constituents was good in the range of their mass concentration (R2≥0.9993). RSD of precision, repeatability, and stability (12 h) were less than or equal to 2.5%. The average recovery rates were from 97.9% to 102.2% and the RSD was in the range of 2.4%～4.6%. The method in this study was rapid, simple, sensitive, stable and reliable. It could be applied for simultaneous determination of nine components in Ligustri Lucidi Fructus, which would provide a reference for the quality control of Ligustri Lucidi Fructus.